2004
DOI: 10.1016/s0896-6273(03)00848-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Caudate Activity by Action Contingency

Abstract: Research has increasingly implicated the striatum in the processing of reward-related information in both animals and humans. However, it is unclear whether human striatal activation is driven solely by the hedonic properties of rewards or whether such activation is reliant on other factors, such as anticipation of upcoming reward or performance of an action to earn a reward. We used event-related functional magnetic resonance imaging to investigate hemodynamic responses to monetary rewards and punishments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

55
380
5
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(448 citation statements)
references
References 51 publications
(3 reference statements)
55
380
5
3
Order By: Relevance
“…Salience activated a network of brain areas involved in arousal, attention, and uncertainty processing, including precuneus, parietal cortex, thalamus, amygdala, and insula (Huettel et al, 2005;Simmons et al, 2004). Salient trials also activated bilateral dorsal striatum, including caudate and globus pallidus, consistent with earlier studies investigating areas that support salience or contingency detection (Tricomi et al, 2004;Zink et al, 2006). By contrast, increasing valence activated a network of brain regions linked to reward representations, including mesial prefrontal cortex , orbitofrontal cortex (O'Doherty et al, 2001;Rolls, 2004), and inferior parietal cortex (Ernst et al, 2004;Glimcher et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Salience activated a network of brain areas involved in arousal, attention, and uncertainty processing, including precuneus, parietal cortex, thalamus, amygdala, and insula (Huettel et al, 2005;Simmons et al, 2004). Salient trials also activated bilateral dorsal striatum, including caudate and globus pallidus, consistent with earlier studies investigating areas that support salience or contingency detection (Tricomi et al, 2004;Zink et al, 2006). By contrast, increasing valence activated a network of brain regions linked to reward representations, including mesial prefrontal cortex , orbitofrontal cortex (O'Doherty et al, 2001;Rolls, 2004), and inferior parietal cortex (Ernst et al, 2004;Glimcher et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Independently manipulating these two factors allowed us to separately examine each factor's influence on NAcc activation. Earlier studies that have focused on valence, using monetary incentives or aversive shock, have not independently varied salience (Abler et al, 2006;Breiter et al, 2001;Jensen et al, 2007;Knutson et al, 2001;Tobler et al, 2007;Tom et al, 2007), while studies that have varied salience have not independently varied valence across gains and losses (Bjork and Hommer, 2006;Jensen et al, 2003;Tricomi et al, 2004;Zink et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another difference with the current study is that in Breiter et al's study, the presented outcomes were not in any way contingent upon the participants' choices, or perceived by participants as such; instead, the participants were simply attending to the various stimulus displays. Importantly, recent research has demonstrated that the perception of action-outcome contingencies has a large impact on the (degree of) involvement of various brain areas in reward processing (Tricomi et al, 2004;Walton et al, 2004;Yeung et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Studies consistently implicate caudate in operant responding [28][29][30][31]. It is suggested that while the caudate represents motor responses necessary for simple operant behaviour, object/ motor features are also represented within ventrolateral PFC to allow for more flexible control over motor responding [9,16].…”
Section: Discussionmentioning
confidence: 99%